Sycp1 Is Not Required for Subtelomeric DNA Double-Strand Breaks but Is Required for Homologous Alignment in Zebrafish Spermatocytes - Imai, Yukiko; Saito, Kenji; Takemoto, Kazumasa; Velilla, Fabien; Kawasaki, Toshihiro; Ishiguro, Kei-ichiro; Sakai, Noriyoshi (Frontiers in Cell and Developmental Biology, 2021)
In meiotic prophase I, homologous chromosomes are bound together by the synaptonemal complex, in which two axial elements are connected by transverse filaments and central element proteins. In human and zebrafish spermatocytes, homologous recombination and assembly of the synaptonemal complex initiate predominantly near telomeres. In mice, synapsis is not required for meiotic double-strand breaks (DSBs) and homolog alignment but is required for DSB repair; however, the interplay of these meiotic events in the context of peritelomeric bias remains unclear. In this study, we identified a premature stop mutation in the zebrafish gene encoding the transverse filament protein Sycp1. In sycp1 mutant zebrafish spermatocytes, axial elements were formed and paired at chromosome ends between homologs during early- to mid-zygonema. However, they did not synapse, and their associations were mostly lost in late zygotene- or pachytene-like stages. In sycp1 mutant spermatocytes, H2AX signals were observed, and Dmc1/Rad51 and RPA signals appeared predominantly near telomeres, resembling wild-type phenotypes. We observed persistent localization of Hormad1 along the axis in sycp1 mutant spermatocytes, while the majority of Iho1 signals appeared and disappeared with kinetics similar to those in wild-type spermatocytes. Notably, persistent Iho1 foci were observed in spo11 mutant spermatocytes, suggesting that Iho1 dissociation from axes occurs in a DSB-dependent manner. Our results demonstrated that Sycp1 is not required for peritelomeric DSB formation but is necessary for complete pairing of homologs in zebrafish meiosis.